A three-dimensional finite-element model of gluteus medius muscle incorporating inverse-dynamics-based optimization for simulation of non-uniform muscle contraction. (January 2021) - Li, Junyan; Marra, Marco A.; Verdonschot, Nico; Lu, Yongtao
Highlights: 3D muscle modelling method for simulating non-uniform contraction in finite element musculoskeletal model was presented. Non-uniform contractile mechanism of gluteus medius muscle is illustrated. The manifestation of anterior, medial and posterior subdivisions of gluteus medius was predicted. Anterior and posterior subdivisions of glutes medius act as antagonists during internal and external rotation. Abstract: Non-uniform contraction exists in many skeletal muscles and plays an important role in the function of the musculoskeletal system. Particularly in the gluteus medius (GM) muscle, its three subdivisions appear activated differently while performing various motion tasks. However, the non-uniform contractile mechanism of GM is poorly understood. In this study, a three-dimensional finite element (FE) model of GM was developed. Non-uniform contraction patterns of the three subdivisions of GM during abduction, internal and external rotation were simulated through an inverse-dynamics-based optimization approach. A set of sensitivity studies were also undertaken to evaluate the influence of parameters including the cost function of optimization and dimension of GM subdivisions on the predicted non-uniform contraction and biomechanics of the muscle. Contraction across GM was found to be highly non-uniform during various motions. The whole GM was activated during abduction, whereas only the anterior and posterior subdivisions were primarily involved in internal and external rotation, respectively. The active contractile stress in a subdivision during abduction was increased if its proportion in GM was expanded. The cost functions of minimizing the sum of active contractile stresses squared/cubed provide similar qualitative predictions of the trend of results. This approach provides the methodological basis to enable simulation of non-uniform muscle contraction using 3D musculoskeletal models.